Interfacial modulation of TiN nanoribbons/graphene oxide for high performance photoactuators. (1st October 2022) - Yang, Bo; Luo, Le; Zhu, Shanshan; Jin, Fengxian; Guo, Sheng-Qi
Abstract: Photoactuators have attracted tremendous scientific attention due to the potential application prospects in sensors, switches, artificial muscles and microelectromechanical devices. However, catering for practical applications, the weak interfacial contact of bilayer limits its further applications. Herein, we focus our investigations on modulating the interface of titanium nitride (TiN) nanoribbons and graphene oxide (GO) by controlling the topography to successful design a high performance photoactuator. In one respect, the surface of TiN nanoribbons was treated by controlling the heating process, forming a uniform dispersion with GO that is convenient for preparing film. Also, the interface between the photothermal conversion layer and passive deformation layer optimized forming close chemical bonds combining. The actuator exhibits fast and reversible actuation performance under the control of light, which only takes 0.8 s to reach the maximum bending. This strategy facilitates unexpected photoactuation with interface engineering, which is expected to further broaden the application prospects of the actuator in smart devices.